Falla ovárica en una yegua de paso fino colombiano: tratamiento combinado homeopático antihomotóxico y hormonal. Reporte de un caso - Otálvaro, Luis J.; Correa, Claudia J.; Velásquez, Carlos E.; Maldonado Estrada, Juan Guillermo (Revista Colombiana de Ciencias Pecuarias, 2009)
Summary Ovulation failure is one of the most frequent causes of infertility in mares. In the present case we report a six-year-old Colombian Paso Fino maiden Mare that was attended for breeding purposes with a previous history of ovulation failure. At ultrasound (US) examination of the reproductive tract and ovaries the left ovary measured 15 x 13 cm and a pathologic 13 x 11 cm diameter anecoic structure was diagnosed. The right ovary was found of normal size, and the uterus was found flacid. An anti homotoxic theraphy with Ovarium compositum®, Damiana injeel®, Cerebrum compositum®, and Phosphor hommacord® for 1½ months and FK (neural) therapy (twice/15 days) were then established, the ovary size was reduced, and softening of the follicular wall and a slight uterine response were observed. After 1½ month, the left ovary had 13 x 11 cm diameter and showed a 9 x 8 cm follicle, whereas the right ovary was multifollicular. Serum progesterone, estradiol and testosterone levels were those characteristics of an anestrous mare. The mare was treated with hCG (3.000 UI, i.v./3 days) and 4 days later a corpus luteum was diagnosed by US in the left ovary and serum progesterone levels raised to 14.91 ng/dl. At day 7 after hCG treatment the mare was given PGF2α (9 μg/kg/for two days) intramuscular, estrous was evident 5 days later, and artificial insemination (AI) with fertile semen was practiced resulting in a viable pregnancy as evaluated by ultrasound at day 20; however, this pregnancy was lost at 40 days after AI. The mare returned to estrus 20 days later, she was then inseminated and the resulting pregnancy was confirmed at day 20th resulting in a successful gestation and foaling of a full term viable foal. This report suggests hormonal therapy and alternative medicine could be successfully combined for treatment of specific ovarian pathologies in mares.